2019
DOI: 10.1186/s13027-019-0228-7
|View full text |Cite
|
Sign up to set email alerts
|

The burden of cancers associated with HIV in the South African public health sector, 2004–2014: a record linkage study

Abstract: Introduction The impact of South Africa’s high human immunodeficiency virus (HIV) burden on cancer risk is not fully understood, particularly in the context of antiretroviral treatment (ART) availability. We examined national cancer trends and excess cancer risk in people living with HIV (PLHIV) compared to those who are HIV-negative. Methods We used probabilistic record linkage to match cancer records provided by the National Cancer Registry to HIV data provided by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 29 publications
4
51
4
Order By: Relevance
“…When compared to data from sub-Saharan African, Nthumba et al reported KS to represent 25% of skin cancers diagnosed in Kenya in 2008 [24]. Although HIV status for subjects was not reported in the current study HIV infection remains the biggest risk factor for developing KS in South Africa [18].…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…When compared to data from sub-Saharan African, Nthumba et al reported KS to represent 25% of skin cancers diagnosed in Kenya in 2008 [24]. Although HIV status for subjects was not reported in the current study HIV infection remains the biggest risk factor for developing KS in South Africa [18].…”
Section: Discussioncontrasting
confidence: 64%
“…e Odds Ratio for PLHIV to develop KS in SA was reported as 134 [18]. PLHIV are also at higher risk for developing NMSC with a 5-fold increased risk of SCC [18,19]. is may also explain the lower BCC to SCC ratio as mentioned.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Other studies examined the management of mental health and substance use disorders [8], or the diagnostic and screening practices for (drug resistant) tuberculosis in adult and paediatric patients [9][10][11]. Furthermore, the routine data collected by participating sites have been enriched in some countries by linking the routine HIV databases to cancer registries [12,13], vital registries [14] or administrative databases [15].…”
Section: Data Collection At Individual and Site Levelmentioning
confidence: 99%